2001
DOI: 10.1152/ajpheart.2001.281.1.h183
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy enhances endothelium-dependent relaxation of ovine uterine artery: role of NO and intracellular Ca2+

Abstract: The present study tested the hypothesis that the pregnancy-associated increase in endothelium-dependent relaxation of the uterine artery was mediated primarily by an increase in nitric oxide (NO) release, resulting in a reduction in smooth muscle intracellular Ca(2+) concentration ([Ca(2+)](i)). Uterine arteries obtained from nonpregnant and near-term (140 days gestation) pregnant sheep were used. The Ca(2+) ionophore A23187 induced endothelium-dependent relaxations in both nonpregnant and pregnant uterine art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
34
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 45 publications
4
34
0
Order By: Relevance
“…Although growth of new vessels as well as remodeling of existing vessels during early pregnancy contributes to the increased UBF, the fact that the period of greatest increase in UBF occurs after the completion of new vessel growth indicates that the maintenance of vasodilation in existing or newly developed vessels is crucial (41). Indirect evidence suggests that pregnancy-and follicular phase-associated elevation in UBF is at least partially mediated by NO (15,22,47).…”
Section: Discussionmentioning
confidence: 99%
“…Although growth of new vessels as well as remodeling of existing vessels during early pregnancy contributes to the increased UBF, the fact that the period of greatest increase in UBF occurs after the completion of new vessel growth indicates that the maintenance of vasodilation in existing or newly developed vessels is crucial (41). Indirect evidence suggests that pregnancy-and follicular phase-associated elevation in UBF is at least partially mediated by NO (15,22,47).…”
Section: Discussionmentioning
confidence: 99%
“…The basal activity of Ca 2ϩ -dependent eNOS of guinea-pig uterine arteries was upregulated fourfold in the course of pregnancy (53). Basal generation of NO was increased in uterine arteries of pregnant animals and attenuated the phenylephrine-induced vasoconstriction (17,29,49,(52)(53)(54). In a previous study of Gokina et al (18), inhibition of basal NO production with N -nitro-L-arginine, a potent inhibitor of NO synthase, significantly enhanced pressure-induced constriction of rat uteroplacental arteries.…”
Section: Increased Basal Camentioning
confidence: 99%
“…acetylcholine; intraluminal pressure; fura-2; manganese quenching NORMAL PREGNANCY is characterized by dramatic and reversible maternal hemodynamic adaptation, including a substantial augmentation of uterine blood flow, which maintains normal oxygen and nutrient delivery to the growing fetus. In late pregnancy, uterine blood flow increases mostly due to considerable growth and remodeling of the maternal uterine vasculature as well as enhanced vasodilation of the uterine arteries in response to chemical or mechanical stimulation (1,3,4,8,9,32,43,45,46,54). Insufficient structural and/or functional vascular adaptation leads to increased uteroplacental vascular resistance with subsequent intrauterine fetal growth restriction (4,43,46).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The adaptations in the uterine circulation to pregnancy are complex and are mediated in part by enhanced vasodilation and vascular remodeling. Previous studies (3,47,54,57) have focused on the endothelial adaptation and have shown an increase in endothelial nitric oxide synthesis/release in the uterine artery during pregnancy. The adaptation of smooth muscle contractile mechanisms is less clear.…”
mentioning
confidence: 99%